STUDI EKSPLORATIF PERILAKU PEMBELIAN PRODUK – PRODUK DI TIGA SITUS BELANJA ONLINE - Imam Nuraryo (Jurnal Komunikasi dan Bisnis, 2018)
The rapid development of Information and Communication Technology has experienced the birth of various kinds in everyday life such as e-commerce activities that currently has spread to various elements of society. Online shopping activities have grown significantly with the interest and interest of people to make purchases online. Consumers today are accustomed to purchases through online shopping sites that arise due to various factors, including product factors, pricing, promotions, easy ways of transacting and communicating via live chat on websites that feature chat, satisfaction, and consumer confidence from sellers on line. This study aims to determine what factors that make consumers. The research approach used is qualitative research method. This study interviewed seven informants who explained about the shopping experience at Lazada, Tokopedia or Shopee and the trust and satisfaction of one of the shopping sites in general. The results of the analysis of this study indicate customer satisfaction with consumer trust and loyalty so that repeat orders from buyers,Keywords: E-Commerce, Customer Satisfaction and Trust, Online Shopping Experience